The Great War & the Middle East a strategic study - Johnson, Robert 1967- (Oxford University Press, 2016)
"The First World War in the Middle East swept away five hundred years of Ottoman domination. It ushered in new ideologies and radicalized old ones--from Arab nationalism and revolutionary socialism to impassioned forms of atavistic Islamism. It created heroic icons, like the enigmatic Lawrence of Arabia or the modernizing Ataturk, and destroyed others. And it completely re-drew the map of the region, forging a host of new nation states, including Turkey, Iraq, Syria, Jordan, Lebanon, and Saudi Arabia - all of them (with the exception of Turkey) under the 'protection' of the victor powers, Britain and France. For many, the self-serving intervention of these powers in the region between 1914 and 1919 is the major reason for the conflicts that have raged there on and off ever since. Yet many of the most commonly accepted assertions about the First World War in the Middle East are more often stated than they are truly tested. Robert Johnson, military historian and former soldier, now seeks to put this right by examining in detail the strategic and operational course of the war in the Middle East. Johnson argues that, far from being a sideshow to the war in Europe, the Middle Eastern conflict was in fact the center of gravity in a war for imperial domination and prestige. Moreover, contrary to another persistent myth of the First World War in the Middle East, local leaders and their forces were not simply the puppets of the Great Powers in any straightforward sense. The way in which these local forces embraced, resisted, succumbed to, disrupted, or on occasion overturned the plans of the imperialist powers for their own interests in fact played an important role in shaping the immediate aftermath of the conflict--and in laying the foundations for the troubled Middle East that we know today"--Publisher description.